Risk Analysis of Chronic Obstructive Pulmonary Disease (COPD) in Barru PLTU Employees - Risma, Risma; Umar, Fitriani; Anggraeny, Rini; Haniarti, Haniarti; Yusuf, Syarifuddin (Jurnal Keperawatan Profesional (KEPO), 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory condition that causes difficulty breathing due to long-term airway obstruction. The purpose of this study was to determine the relationship between age, nutritional status, medical history, knowledge, smoking status, and use of Personal Protective Equipment (PPE) on the risk of COPD in Barru PLTU employees. This study was a quantitative analytical study with a cross-sectional design. The sample of this study was part of the employees at PT. Indonesia Power (IP) PLTU Barru Unit in the ASH Yard (coal management), Coal Yard (boiler), Cleaning Service Unit, and Security sections totaling 80 employees. Sampling used the simple random sampling method. The collected data were processed and presented in the form of descriptive, narrative or explanatory tables using the Statistical Package for Social Sciences (SPSS) version 25 program. The analysis used was univariate and bivariate using the Chi-square test. There was a relationship between age (p-value <0,001), nutritional status (p-value <0,001), knowledge (p-value <0,001) and use of PPE (p-value <0,001) on the risk of COPD in Barru PLTU employees and there was no relationship between medical history (p-value = 0,079) and smoking status (p-value = 0,491) on the risk of COPD in Barru PLTU employees. It was recommended that employees pay attention to the SOP for using PPE to prevent the risk of COPD and employees aged ≥ 40 years who are at risk are expected to always pay attention to their body's immunity.